Analisis Penerimaan Pasien terhadap Mobile JKN pada Fitur Pendaftaran Rawat Jalan dengan Metode TAM Di RSKIA PKU Muhammadiyah Kotagede Yoyakarta Tahun 2026 - Hanandra Dwinda Savitri; Frestiany Regina Putri; Sri Wulandari (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation in the healthcare sector has accelerated the adoption of technology-based service innovations, including the Mobile JKN application, which provides an online outpatient registration feature. The successful implementation of this application depends not only on the availability of the system but also on users' acceptance of the technology. This study aimed to examine the effects of perceived usefulness, perceived ease of use, and behavioral intention on user acceptance of the outpatient registration feature in the Mobile JKN application using the Technology Acceptance Model (TAM). A quantitative study with an analytical research design was employed. A total of 85 BPJS Kesehatan participants who had used the Mobile JKN application were selected as respondents through purposive sampling, while the sample size was determined using the Slovin formula. Data were collected using a validated and reliable questionnaire and analyzed through multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The findings revealed that perceived usefulness, perceived ease of use, and behavioral intention had positive and statistically significant effects on user acceptance, both individually and simultaneously. Among these variables, behavioral intention was identified as the strongest predictor of user acceptance. Furthermore, the coefficient of determination (R²) of 0.511 indicated that the proposed model explained 51.1% of the variance in user acceptance of the Mobile JKN outpatient registration feature, while the remaining 48.9% was attributable to factors beyond the scope of this study.